Effect of Probiotic Supplementation After Laparoscopic Sleeve Gastrectomy on Constipation and Gastrointestinal Quality of Life - Yıldız, Nida; Baş, Murat; Coşkun, Halil; Yardımcı, Erkan; BATAR, NAZLI (Doç. Dr. Mustafa Hasbahçeci, 2021)
In this study, we aimed to investigate the early effect of probiotic supplementation after Laparoscopic Sleeve Gastrectomy (LSG) on constipation and gastrointestinal quality of life compared to control group. Methods: This study was a prospective, randomized clinical trial. Participants were recruited to Bariatriklab Obesity and Metabolic Surgery Center for LSG. All patients were divided into 2 groups as probiotic and control by using simple randomization. The probiotic group consumed Bifidobacterium animalis lactis BB-12 strain as a probiotic supplement during 6 weeks after LSG. Gastrointestinal Symptom Rating Scale (GSRS), Constipation Severity Instrument (CSI), Patient Assessment of Constipation Quality of Life Scale (PAC-QOL), Bristol Stool Form Scale (BSFS), Gastrointestinal Quality of Life Index (GIQLI) of the patients were recorded before LSG and at the 2nd, 4th, 6th weeks after LSG. Results: The probiotic group had an average age of 37.00±8.92 years (18 female, 12 male), the control group had an average age of 41.03±11.29 years (23 female, 7 male). CSI (16.50 ± 14.76 vs. 31.37 ± 15.34), PAC-QOL (58.53 ± 12.59 vs 72.30 ± 19.70), GSRS (26.83 ± 9.14 vs. 37.93 ± 16.59) and total score mean were lower compared to the control group, GIQLI total score average (147.50 ± 11.79 vs 136.87 ± 18.98) was found higher (p <0.05) in probiotic group. Conclusion: Probiotic supplementation improved the constipation and gastrointestinal quality of life in the early post-LSG period in the probiotic group compared to the control group.
Laparoskopik Sleeve Gastrektomi Sonrası Probiyotik Takviyesinin Konstipasyon ve Gastrointestinal Yaşam Kalitesi Üzerine Etkisi
Keywords: Bariatric Surgery; Gastrointestinal Quality of Life; Constipation; Sleeve Gastrectomy; Probiotics